On the role of vegetation density on net snow cover radiation at the forest floor. Issue 15 (12th August 2013) - Seyednasrollah, Bijan; Kumar, Mukesh; Link, Timothy E.
Abstract : [1] The timing and amount of snowmelt from forested watersheds is influenced by the total radiation reaching the forest floor. In order to understand and predict the impact of natural or anthropogenic changes in vegetation density on snow energetics, it is important to first quantify the relationship between vegetation density and net snow cover radiation. A physically based forest radiation model (FoRM) was developed to quantify net radiation on the forest floor and its dependence on vegetation density in midlatitude coniferous forests. For clear sky conditions, net radiation on the horizontal forest floor frequently exhibits a nonmonotonic decreasing then increasing trend with increasing vegetation density. The relationship turns monotonically increasing when cloudiness is considered. Variations in slope and aspect were also found to influence the behavior of radiation in relation to changing vegetation density. Net radiation increases with increasing slope for southerly aspects and decreases with northerly facing aspects. For clear sky conditions on south facing slopes, the optimal vegetation density at which radiation is minimized increases both with slope and toward more southerly aspects. In contrast, on north facing slopes, the vegetation density where net radiation is minimized decreases with increasing slope angle. When sky cloudiness is considered, for increasing south facing slopes, the relationship becomes relatively complex with the appearance of a local minimum at intermediate vegetation densities. The results have implications for prediction of snowmelt dynamics in complex terrain and development of forest thinning strategies to modulate snowmelt timing in mountainous environments. Key Points: Forest floor radiation (FFR) shows a u‐shaped trend with vegetation density. FFR increases/decreases with increasing slope for southerly/northerly aspects. Increasing cloud cover results in monotonic increase in FFR on northerly slopes.